Upaya Peningkatan Pengetahuan Terhadap Kasus Osteoarthritis Knee Pada Komunitas Ibu-Ibu Pemberdayaan Kesejahteraan Keluarga (PKK) Di Wilayah Binaan Puskesmas Banyuanyar - Izdihar Zahra; Arif Pristianto; Seliana Sinta Debi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Background: Osteoarthritis is a degenerative disorder that occurs in the articular cartilage characterized by reduced synovial joints, the formation of osteophytes, damage to the ligaments and changes in the bones. The cause of osteoarthritis in the area of Puskesmas Banyuanyar is 46% of the population in one card families still have families who smoke and as much as 22% of people do not do physical activity due to the busy and physical condition. Objective: This investigation was carried out in an effort to improve knowledge on the case of osteoarthritis in the area of Puskesmas Banyuanyar. Method: This activity is a form of dissemination using leaflet media. To find out the results of improved understanding researchers conduct evaluations of pre-implementation and post-implementation. Results: Public dedication through this method of dissemination resulted in increased knowledge in the case of osteoarthritis from the average value of knowledge of 4,4% to 97,6%. Conclusion: Based on the results of the implementation of public service activities such as efforts to improve knowledge in case of osteoartritis, there was an increase in knowledge in PKK community